Semi-synthesis and evaluation of fusidic acid derivatives as potential antituberculosis agents - Shanika, Petrus Siningu (Department of Chemistry, 2018)
The causative agent of tuberculosis (TB), Mycobacterium tuberculosis (Mtb), still remains one of the most serious infectious diseases with 10 million new reported cases in 2015. Although TB is curable, the ability to acquire resistance to various antibiotics by the Mtb organism is well known. The emergence and spread of multidrug resistance (MDR) and extremely drug resistance (XDR) Mtb strains, along with HIV/TB co-infections, has put TB control programmes in jeopardy, particularly in developing countries. Therefore, there is a continuous need to search for new structural classes of anti-TB drugs with novel modes of action and ideally no cross resistance to current drugs to treat both sensitive and resistant forms of TB. Fusidic acid is a naturally occurring antibiotic used to treat Gram-positive bacterial infections. It has potent activity against S. aureus and is clinically used to treat mild to moderately severe skin and soft-tissue infections. The mode of action of fusidic acid involves the inhibition of protein synthesis via binding to bacterial elongation factor G (EF-G). Fusidic acid has also been reported to possess in vitro antimycobacterial activity but was subsequently found to lack in vivo efficacy in a mouse model. Towards contributing to new antimycobacterial agents, this study focusses on repositioning fusidic acid for tuberculosis by employing prodrug and bioisosterism approaches through structural modifications at the C-3, C-11 and C-21 positions of the drug.